Effect of insulin levels and plasma fasting glucose on refractive status in the United States population aged 12–19 years - Hu, Pengcheng; Liu, Jialing; He, Ming; Fu, Yuxian; Wang, Menglei (Frontiers in Medicine, 2023)
The causes of myopia are varied, and both genetic and environmental influences play an essential role. The prevalence of myopia is increasing among adolescents and is expected to be more than one-third the global population by 2050. Some animal studies suggest that hyperinsulinemia may be a cause of myopia. In this context, the purpose of this paper is to investigate the potential effects of insulin levels and plasma fasting glucose on the refractive status of adolescents. Methods: Data were collected from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2008. Weighted multivariable linear regression models were used to assess the effect of insulin levels, plasma fasting glucose on refractive status. We used a smooth curve fit to reveal the nonlinear relationship between the variables.In the multivariate regression model, as insulin levels increased, there was a shift towards myopia in refractive status (β = -0.013, 95% CI: -0.023 to -0.004). This correlation was also evident in the male adolescent subgroup (β = -0.021, 95% CI: -0.035 to -0.007). Similar findings indicated that in Mexican Americans, there was a myopic shift in refractive status as insulin levels increased (β = -0.018, 95% CI: -0.033 to -0.002). However, grouping by differences in insulin measurement showed no significant correlation in Mexican-Americans. At the same time, there was no significant correlation between plasma fasting glucose and refractive status (β = -0.041, 95% CI: -0.174 to 0.091). This is a provisional file, not the final typeset articleThe present cross-sectional study demonstrated that higher insulin levels may promote the development of myopia in adolescents, but there may be variations across gender and ethnicity.More basic research is needed to reveal the mechanistic reasons for the association.